A new place for eternal rest: The extramural pantheon and the funerary culture of Ayaviri between 1830 and 1940 (Melgar-Puno) - Saavedra Ordinola, Deyvi (2021)
The first cementeries located outside of the city walls of Peru display transformations as well as continuities in local mentalities and practices regarding death, which we can observe in different cities, such as Ayaviri in northern Peru. The first analysis of the subject describes the first century of these unique cemerery practices, particularly with regard to management, funereal art and rituals, as well as makes comparison with like cases in other cities.